ANALISIS EFISIENSI PENGGUNAAN PUPUK NITROGEN PADA PADI SAWAH DI TANAH INCEPTISOLS - -, Herniwati; Nappu, M. Basir (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2018)
Nutrient management strategies effectively and efficientlyis an additional effort to improvethe results obtaained by farmers and related to environmental sustainability. The use of N fertilizer, which is an essential nutrient for rice plants, needs to know the optimum dosage according to plant needs and soil fertility. The research objective is to determine the optimum N dose to get the maximum rice yield in irrigated paddy fields. The study was conducted in Matoangin, Bantimurung District, Maros, South Sulawesi, for two planting seasons, from January to August 2014. The first planting season lasted from January to April 2014 (rainy season), and the second planting season from May to August 2014 ( dry season). The experiment were used in a randomized block design with three replications. The dosage of N fertilizer consists of six levels, namely (N0) without fertilizer; (N1) 33.75 kg N / ha equivalent to 75 kg Urea / ha; (N2) 67.50 kg N / ha equivalent to 150 kg Urea / ha; (N3) 101, 25 kg N / ha equivalent to 225 kg Urea / ha; (N4) 135 kg N / ha equivalent to 300 kg Urea / ha, and farmer dose (N5) 168.75 kg N / ha equivalent to 375 kg Urea / ha. The results showed plant height, panicle length, number of filled grain and yields of Inpari-4 rice at the study site were influenced by N fertilization. Research in the rainy and dry season showed fertilization N increased growth and yield of rice by following a quadratic pattern, and dosage the optimum N fertilizer is different in each season. The optimum N fertilizer requirements to obtain the maximum results in the rainy season (6.78 t / ha) is 129 kg N / ha equivalent of 282 kg of urea / ha, while in the dry season takes 131.57 kg N / ha equivalent of 286 kg urea / ha to get maximum yield (7.15 t / ha). The dosage of fertilizer is more efficient compared to that applied by farmers, namely> 300 kg urea / ha (equivalent to 135 kg N / ha).